In memoriam Lieutenant Colonel Professor Ahmad Ghazali Abu Hassan (1956-2022) - Teh Yik Koon,; Aruna Devi Gopinath,; Ariffin S.M Omar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In this obituary note, we dedicate our thoughts to the late Lieutenant Colonel Professor Ahmad Ghazali Abu Hassan (1956-2022), who recently passed away. His demise in December 2022 is a great loss to the nation and the academia, especially in the Defence and Strategic Studies. To many of us who believed in him, we know he cared for all irrespective of race, creed, or religion. Every footprint he has left behind becomes an imprint in our lives. His memory will live on in the hearts and minds of his friends, colleagues, students, and all those he had inspired. May his soul rest in peace.